Optimizing New Student Data Collection Through Basic Education Data Implementation: Optimalisasi Pendataan Peserta Didik Baru Melalui Implementasi Data Pokok Pendidikan - Khoirun Nisa; Isnaini Rodiyah; Intan Ardila Sari; Abdul Qodir; Karinda Wustoto; Winda Fitri Lestari (International Consortium of Education and Culture Research Studies, 2025)
General Background Basic education data systems serve as primary databases for managing educational information across all school levels. Specific Background The implementation of basic education data aims to provide accurate, up-to-date, and integrated information to support planning, budgeting, and policymaking in the educational sector. Knowledge Gap Despite its potential, practical application encounters various challenges regarding data validity, accuracy, trained human resource shortages, and inadequate technological infrastructure. Aims This qualitative case study analyzes the implementation of basic education data for new student data collection at SMA Negeri 1 Porong using George Edward III's theoretical framework. Results Findings demonstrate that a well-defined bureaucratic structure with clear standard operating procedures and competent human resources supports smooth implementation, whereas limited internet infrastructure and stakeholder participation remain primary hurdles. Novelty This research specifically evaluates how hierarchical communication channels and institutional standard operating procedures govern public policy execution within secondary school databases. Implications Educational institutions must invest in continuous technological infrastructure maintenance and regular strategy evaluations to ensure data reliability and support evidence-based decision-making. Highlights: Well-defined bureaucratic structures characterized by clear standard operating procedures significantly support smooth administrative execution. Competent and enthusiastic human resources serve as crucial drivers for successful information system management. Limited information and communication technology infrastructure alongside participant engagement present ongoing operational challenges. Keywords: Policy Implementation, Basic Education Data, Bureaucratic Structure, Resource Availability, Data Collection